Molecular Cytogenetic Characterization of two Triticum–Secale–Thinopyrum Trigeneric Hybrids Exhibiting Superior Resistance to Fusarium Head Blight, Leaf Rust, and Stem Rust Race Ug99 - Dai, Yi; Duan, Yamei; Liu, Huiping; Chi, Dawn; Cao, Wenguang; Xue, Allen; Gao, Yong; Fedak, George; Chen, Jianmin (Frontiers in Plant Science, 2017)
Fusarium head blight (FHB), leaf rust, and stem rust are the most destructive fungal diseases in current world wheat production. The diploid wheatgrass, Thinopyrum elongatum (Host) Dewey (2n = 2x = 14, EE) is an excellent source of disease resistance genes. Two new Triticum-Secale-Thinopyrum trigeneric hybrids were derived from a cross between a hexaploid triticale (X Triticosecale Wittmack, 2n = 6x = 42, AABBRR) and a hexaploid Triticum trititrigia (2n = 6x = 42, AABBEE) , were produced and analyzed using genomic in situ hybridization and molecular markers. The results indicated that line RE21 contained 14 A-chromosomes, 14 B-chromosomes, 3 pairs of R-chromosomes (4R, 6R and 7R), and 4 pairs of E-chromosomes (1E, 2E, 3E and 5E) for a total chromosome number of 2n = 42. Line RE62 contained 14 A-chromosomes, 14 B-chromosomes, 6 pairs of R-chromosomes, and 1 pair of translocation chromosomes between chromosome 5R and 5E, for a total chromosome number of 2n = 42. At the seedling and adult growth stages under greenhouse conditions, line RE21 showed high levels of resistance to FHB, leaf rust, and stem rust race Ug99, and line RE62 was highly resistant to leaf rust and stem rust race Ug99. These two lines (RE21 and RE62) display superior disease resistance characteristics and have the potential to be utilized as valuable germplasm sources for future wheat improvement.